PENGARUH MOTIVASI DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI DI SEKRETARIAT DAERAH KOTA BOGOR - Syaiful Anwar; Muchammad Hamdani; Dwi Oktiana Irawati; Fitria Agustina Suryani (Institut Teknologi dan Bisnis Dewantara, 2025)
This study aims to analyze the influence of motivation (X1) and work discipline (X2) on employee performance (Y) at the Bogor City Regional Secretariat. The research method used is quantitative with a descriptive and verificative approach, collecting data through observation and distributing questionnaires to employees. The sample in this study includes all employees at the Bogor City Regional Secretariat, totaling 129 people, to fill out the motivation and work discipline variables, with one leader filling out the employee performance variable. The data were analyzed using validity and reliability tests, as well as multiple linear regression analysis with the help of SPSS software. The results of the study indicate that motivation and work discipline, both partially and simultaneously, have a significant effect on employee performance, as evidenced by the F-test result of 5.303 with a significance level of 0.03. This means that the higher the motivation and work discipline, the better the employee performance will be.